Agroecological family farming in Uruguay, innovative and counter-hegemonic contributions to sustainability - Gómez Perazzoli, Alberto; Gazzano , Inés; Dieguez Cameroni, Francisco (Agrociencia Uruguay, 2024)
Agroecological family farming in Uruguay has a background of over thirty years and is increasingly recognized as a valid option for the transformation of the food system. However, basic and comprehensive information on the sector is not available. The information collected by the Agroecology Network of Uruguay in 2020 and 2021 was systematized, being this organization the only one that certifies for the domestic market, through a Participatory Guarantee System. The results obtained allow defining several aspects of the sector. The number of certified properties increased 120% between 2012 and 2021. The sale of organic food, mainly vegetables, reached USD 6.4 million in 2021 and grew 2.1 times between 2012 and 2021. Ninety-two percent of the properties are family-owned. Women's participation in the ownership of farms is 42%, which is higher than the national average. Production is distributed among 111 different species. Seventy-five percent of the farms produce their own seeds and 87% have wild areas for conservation. The most common soil management practices are the use of green manures, crop rotation, and the use of compost and biofertilizers. Direct-to-consumer sales channels are mostly used. For the first time, comprehensive information representative of the domestic market for organic food in the country is presented. Hopefully, these contributions will be useful in understanding the transition processes in agroecology, and in order to support the definition of the agendas of various actors linked to agroecology.